Clinical Pharmacology Characterization of the First‐In‐Class Oncolytic Viral Therapy T‐VEC in Adults and Pediatric Subjects. - Zhang, Xinwen; Balu, Bhavya; Chen, Po‐Wei; Mehta, Khamir; Li, Chuang; Upreti, Vijay V. (Journal of Clinical Pharmacology, 2026)
Oncolytic viruses are an emerging class of immunotherapies for cancer treatment. Talimogene laherparepvec (T‐VEC) is a first‐in‐class oncolytic virus approved globally for advanced melanoma. Herein, we describe the quantitative clinical pharmacology aspects of T‐VEC that supported the development of this unique therapy. As a live therapy, the exposure characteristics of T‐VEC are vastly different from the pharmacokinetics (PK) of traditional small molecules or therapeutic proteins and were characterized as tumor site oncolytic viral kinetics. Relatively flat relationships between T‐VEC dose, lesion exposures, and efficacy were identified based on dose–exposure–response (D‐E‐R) analyses of 60 adult subjects, indicating that optimal drug effect was achieved over the studied dose range (106‐108 plaque forming unit [PFU]/mL); hence, efficacy was not sensitive to dose variations within the range. The relatively flat D‐E‐R relationship for T‐VEC was also beneficial for biopharmaceutic aspects unique for live viruses, including bridging small variations in viral infectivity observed from batch to batch during manufacturing. Additionally, the exposures in pediatric subjects (N = 15) were within the range, although generally lower in medians than adults (N = 60). The primary safety concern of T‐VEC‐related herpetic infection was evaluated using a mechanistic PK‐PD model which indicated minimal infection risk over the up to 5 years follow‐up duration. Overall, T‐VEC demonstrated favorable PK‐PD profiles and was well tolerated in adults and pediatric subjects at the approved dosing regimen. Quantitative clinical pharmacology analyses have supported the optimal development of T‐VEC and are poised to accelerate the development of these promising therapeutic oncolytic viruses.